Use of Problem-Based Learning Methods in the Structure of Negotiation Texts for Class X Students of SMA Negeri 1 Sipirok - Aritonang, Devinna Riskiana; Dewi, Shoufi Nisma (Jurnal Hata Poda, 2024)
AbstractThis research aims to determine the use of Problem Based Learning Methods in the structure of negotiation texts for class X students of SMA Negeri 1 Sipirok for the 2022-2023 academic year. This research method uses a qualitative method with a descriptive approach. The research informants consisted of: 36 class X SMA Negeri 1 Sipirok students and one teacher. The data analysis techniques used start from reducing data, presenting data, and drawing conclusions. The results of data analysis found that from the conceptual understanding of data I, there were only 16 students who did not complete. Student learning mastery in data I has an average score of 65.38 with a percentage of 70.22% in the "High" category. Furthermore, the conceptual understanding of data II brings out the complete learning outcomes of all students in data II which has an average value of 95.97 with a percentage of 100% in the "Very High" category. A comparison of the two learning methods can be a positive contribution in developing the learning process in the classroom, especially in conceptual understanding of the structure of negotiation texts. Keywords: Use, Problem Based Learning Method, Conceptual Understanding, Structure, Negotiation Text.